A rapid spectrophotometric method for the determination of mercury in environmental, biological, soil and plant samples using diphenylthiocarbazone. Issue 1 (2003) - Ahmed Ahmed, M. Jamaluddin M. Jamaluddin; Alam Alam, Md. Shah Md. Shah
Abstract : A simple, sensitive and highly selective direct spectrophotometric method for the determination of trace levels of mercury(II) in various samples is described. Diphenylthiocarbazone (dithizone) reacts in slightly acidic 50% aqueous 1, 4-dioxane media (0.18–1.80 M sulphuric acid) with mercury(II) to give an orange chelate which has an absorption maximum at 488 nm. The average molar absorption co-efficient and Sandell's sensitivity were found to be 2.5×10 4 l mol −1 cm −1 and 0.015 μg of Hg(II) cm −2, respectively. The reaction is immediate and absorbance remains stable for over 24 h. Beer's law is obeyed for concentration range of mercury(II) between 0.1 μg ml −1 and 25 μg ml −1 ; the stoichiometric composition of the chelate is 1 :2 (mercury : dithizone). The various analytical parameters, such as effect of time, acidity, reagent concentration and foreign species, were studied. The method was applied successfully to a number of environmental waters (portable and polluted), biological samples (human blood, urine and fish), soils, plant samples (potato, cabbage, lettuce, carrot and tomato), solutions containing both mercury(I) and mercury(II) and complex synthetic mixtures. The method is very simple and requires no solvent extraction or pre-concentration steps.